When idealists evade taxes: the influence of personal moral philosophy on attitudes to tax evasion – a Lebanese study. (April 2014) - Sidani, Yusuf M.; Ghanem, Abdul Jalil; Rawwas, Mohammed Y. A.
<x xml:space="preserve">Abstract</x> This paper explores attitudes regarding tax evasion and the relationship between personal moral philosophy and such attitudes in a weak tax environment. The results confirm the multidimensionality of tax evasion attitudes. Idealism was negatively related to self‐interest tax evasion attitudes while relativism was positively related to such attitudes. Idealism was also positively related to tax evasion attitudes stemming from concerns about the justice of the tax system. Idealists in a weak tax environment seemingly go through a cognitive reframing process where they recognize that the tax system is unfair, and accordingly tax evasion is a way to serve a different moral absolute, that is of equity, rather than another different moral absolute, which is fulfilling obligations to governments. The results are also explained in light of the suggested low moral intensity of tax evasion among respondents. Policy implications are presented.